(3QSGdI aj GdYQhVs
(3ChdgG (B:s
(3Cf jchf dG MSfkG bGdhG ai GdQhH s
(3BNQgG (B:s
(3hgPG eYfi bhdg gPg Pjd jJYdb HgG Ydi MSH GdWdGbI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdgG hbajI HGSe edG YHO Gddg GdYHOdi Ydi ChdGOg hjQLY JGQjNgG Edi SfI (B1239 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs